ANATOMI KONSEP PENYELESAIAN KONFLIK AGRARIA: STUDI PERBANDINGAN ANTARA RANAH KEBIJAKAN DAN RANAH PERJUANGAN AGRARIA - Kus Sri Antoro (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2013)
This article is a conceptual idea of the comparison between a research finding and reality in the community relatedto the agrarian conflict resolution. The study is entitled Resolution Policy on Contemporary Agrarian Conflict, which is one of thesystematic studies carried out by STPN in 2012; while the aforementioned reality in the society is gathered from records of thedynamics of agrarian conflict and struggle in several areas collected by Forum Komunikasi Masyarakat Agraris (FKMA), which arepublished by FKMA and other official media. By exploring and comparing the conceptual ideas of the two written sources, thisarticle is intended to map out the approaches and models of agrarian conflict resolution, especially according to the perceptionsand interests of the three actors of agrarian political economy, namely the state, market and society.Keywords: agrarian resources, conflict, conflict resolution